2005
DOI: 10.1177/026248930502400101
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene-Kevlar Composite Foams III: Torsion Properties

Abstract: High density closed-cell Kevlar-polyethylene composite foams (17 - 30% void fraction) were prepared by compression molding and characterized via torsion rectangular tests in order to determine the effect of thin unfoamed skins and Kevlar content on shear modulus. It was found that structural foam models gave better results than uniform foam models indicating that thin skins have an important effect on the shear modulus of polymer foams. The normalized modulus of our composite structural foams can be predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…S ) of the WPC foams are compiled in Figure 3. According to Zhang and Rodrigue [16], the modulus of foamed composites is proportional to that of comparable unfoamed ones for all strain rates. They concluded that both foamed and unfoamed samples behave in a similar manner.…”
Section: Specific Complex Shear Moduli (G ãmentioning
confidence: 91%
“…S ) of the WPC foams are compiled in Figure 3. According to Zhang and Rodrigue [16], the modulus of foamed composites is proportional to that of comparable unfoamed ones for all strain rates. They concluded that both foamed and unfoamed samples behave in a similar manner.…”
Section: Specific Complex Shear Moduli (G ãmentioning
confidence: 91%
“…Several models have been proposed to predict this ratio as a function of morphological parameter like reduced density and skin thickness. The tensile moduli of our PP foams as presented in Table 2 are now compared with mechanical models presented next where more details can be obtained in previous reports (17)(18)(19)(20)(21)(22) . For the moment, no models are available to predict other tensile properties like yield stress, stress at break, elongation at break, etc.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Finally, there is a densification phase when the network is collapsed onto itself and contact between network elements, which results in dramatic stiffening of the material. Although actual cell microstructure is very complicated, these regimes of deformation have been studied extensively and significant understanding has been obtained using idealized models 3–9. Currently, the quite popular theoretical model used to predict the compression properties of low density foams was put forth by Gibson and Ashby,2 which shows that in idealized cubic cell model the mechanical properties are closely relative to the foam relative densities and material properties, which is further proved by many experimental results 1, 10, 11.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, the quite popular theoretical model used to predict the compression properties of low density foams was put forth by Gibson and Ashby,2 which shows that in idealized cubic cell model the mechanical properties are closely relative to the foam relative densities and material properties, which is further proved by many experimental results 1, 10, 11. For high density foams, Moore et al proposed an empirical expression for the modulus of polypropylene foams 5. In compression process, a particularly unusual aspect of foams is the large capacity to absorb energy, which stems from the large deformation of cell walls and edge.…”
Section: Introductionmentioning
confidence: 99%